PENDEKATAN PERUBAHAN TINGKAH LAKU SISWA DALAM PERSPEKTIF AGAMA HINDU - Nanda Jaya Pratama, I Gede; Ni Komang Sutriyanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Changing behavior in students is one of the challenges for teachers who are professionals with the task of educating students apart from teaching and also transforming the knowledge possessed by a teacher in various fields. The changes in behavior that occur in today's students can be seen from the decline in morals which is accompanied by the lack of śraddha and devotion of students as religious people, especially those who are Hindu. The Vedas as the holy book of Hindus not only guide religious life but also provide guidance for the life of the people in various fields, one of which is in the scope of education. Vedic teachings have also provided guidelines for the relationship between teachers and students. Changes in student behavior from a Hindu religious perspective can lead to positive or negative actions. In classroom management, teachers must master the problem of changes in student behavior that lead to negative actions. In connection with this problem, this research examines approaches that can be applied by a teacher to change students' character in a positive direction from a Hindu religious perspective. This research is of a qualitative type with descriptive research methodology. The results of this research are that three approaches are by the Hindu religious perspective, namely: 1.) Authoritarian Approach; 2.) Emotional Approach; and 3.) Attitude Approach.